ANALISIS COMMON-SIZE UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAAN PADA PT XL AXIATA TBK DAN PT SMARTFREN TELECOM TBK YANG TERDAFTAR DI BEI PERIODE 2018 - 2020 - Ningsih, Widia Ningsih Alfiany (Jurnal Riset Mahasiswa Akuntansi, 2023)
The research that has been done can be shown to determine the company's financial performance by using the common-size statement analysis method at the companies PT XL Axiata, Tbk and PT Smartfren, Tbk. Those listed on the Indonesia Stock Exchange in the period 2018 to 2020 are seen from the balance sheet and income statement. This research is quantitative descriptive. In collecting the data using the documentation method and in analyzing the data with the common-size analysis. Based on the results of the common-size analysis seen from the balance sheet of PT XL Axiata, Tbk in allocating its funds for assets part of the debt of PT Smartfren Telecom, Tbk. in allocating the use of assets from own capital, therefore increasing the margin of safety for creditors and can strengthen the statement of financial position. Then the common-size is seen from the income statement at PT XL Axiata, Tbk and PT. Smartfren Telecom experienced a decline in its net profit during the 2018 – 2020 period, therefore its financial performance was not good. However, in the 2020 period financial performance has increased in terms of net income, therefore the financial performance is getting better.